EFFECTS OF SUPPLEMENTING COLOS24H GROW PLUS 2+ ON NUTRITIONAL STATUS AND HEALTH OF PRESCHOOL CHILDREN - Pham , Quoc Hung; Ta , Ngoc Ha (Tạp chí Y học Việt Nam, 2023)
A controlled intervention study to evaluate the effect of formula supplementation on nutritional status and health of preschool children aged 36-59 months was completed in Ninh Binh province in August 2023 with 110 subjects. The intervention group (55 subjects) used formula supplementation twice daily for 2 months and the control group (55 subjects) used a regular diet. Results showed positive effects comparing the intervention group vs. the control group: Improved average weight: increased 0.18 kg (0.31 ± 0.06 vs. 0.13 ± 0.07 kg) after 1 month; increased 0.43 kg (0.70 ± 0.08 vs. 0.27 ± 0.03 kg) with statistical significance (p<0.05) after 2 months. Improved average height after 2 months: increased 0.36 cm (1.44 ± 0.17 vs. 1.08 ± 0.26 cm) with p<0.05. Reduced the risk of malnutrition and malnutrition 27.3% (49,1% vs. 21,8%) with p<0.05; Reduced underweight malnutrition 9,1% (16,4% vs. 7,3%) with p<0.05. Reduced health problems: respiratory infections (3.6%); diarrhoea (1.8%); constipation (5.5%); anorexia (12.7%); difficulty sleeping (14.5%) but not statistically significant (p>0.05). Product acceptability was high with 92.8% used full dosage.